Fantasy lover eaudiobook - Kenyon, Sherrilyn (Dark-Hunter: Were-Hunter, 2017)
Dear Reader, Being trapped in a bedroom with a woman is a grand thing. Being trapped in hundreds of bedrooms over two thousand years isn't. And being cursed into a book as a love-slave for eternity can ruin even a Spartan warrior's day. As a love-slave, I know everything about women. How to touch them, how to savor them, and most of all, how to pleasure them. But when I was summoned to fulfill Grace Alexander's sexual fantasies, I found the first woman in history who saw me as a man with a tormented past. She alone bothered to take me out of the bedroom and onto the world. She taught me to love again. But I was not born to love. I was cursed to walk eternity alone. As a general, I had long ago accepted my sentence. Yet now I have found Grace—the one thing my wounded heart cannot survive without. Sure, love can heal all wounds, but can it break a two-thousand-year-old curse? Julian of Macedon